Laminated optical film and image display device
Patent Information
- Application Number
- JP2023145373
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
Smart Images

Figure 2025038640000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated optical film having at least an acrylic film and a first optical film laminated via an adhesive layer, which can be used to form image displays such as mobile phones, car navigation devices, personal computer monitors, and televisions. [Background technology]
[0002] Image display devices such as mobile phones, car navigation devices, PC monitors, and televisions are equipped with laminated optical films in which multiple optical films are laminated via adhesive layers or pressure-sensitive adhesive layers. Polarizers and transparent resin films such as acrylic films are used as the optical films.
[0003] Regarding acrylic films, since there are almost no functional groups on the film surface that can contribute to improving adhesive strength, there is a concern that the adhesive strength between the acrylic film and other optical films will be insufficient when the film is made into a laminated optical film. In response to this, the following Patent Document 1 describes an optical film laminate in which a (meth)acrylic resin layer and a thermoplastic resin film such as a cycloolefin resin film are bonded together with sufficient adhesive strength by an active energy ray curable adhesive, and which is lightweight and has a thin film. The adhesive layer is formed of an active energy ray curable adhesive containing 2 to 35 parts by weight of a polymerizable monomer that dissolves the (meth)acrylic resin layer and 30 to 60 parts by weight of a polymerizable multifunctional acrylate compound, relative to a total of 100 parts by weight of the active energy ray curable compound containing a polymerizable monomer that dissolves the (meth)acrylic resin layer and a polymerizable multifunctional acrylate compound. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-232251 A Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, in recent years, a durability test required for laminated optical films used for in-vehicle applications is, for example, a humidity durability test in which the film is exposed to an environment of 65°C and 95% humidity for 1000 hours. Here, the present inventors have studied in detail the appearance state of the laminated optical film after such a humidity durability test, and have found that bright spots due to white hazy foreign matter occur especially at the end of the laminated optical film, resulting in a defective product in terms of appearance characteristics. This phenomenon is observed for the first time after a durability test under a high temperature and high humidity environment, and it was necessary to make a new and intensive study to solve the problem.
[0006] The present invention has been developed in consideration of the above-mentioned circumstances, and aims to provide a laminated optical film which comprises at least an acrylic film, in which the occurrence of bright spots caused by foreign matter is suppressed even after a humid durability test, and which has excellent appearance characteristics and excellent adhesive strength between laminated optical films. [Means for solving the problem]
[0007] The above problem can be solved by the following configuration: That is, the present invention provides a laminated optical film in which at least an acrylic film and a first optical film are laminated via an adhesive layer, the adhesive layer being formed of a cured layer of an adhesive composition containing at least a polymerizable compound, the acrylic film and the adhesive layer having a structure in which they are in direct contact with each other, the logPow representing an octanol / water partition coefficient based on a weighted average of the molar fraction of the polymerizable compound contained in the adhesive composition being 1.8 or more and 3.0 or less, and the elastic modulus of the adhesive layer being 1×10 5 Pa or more and 3×10 6 The laminated optical film (1) has a compressive strength of 0.1 Pa or less.
[0008] In the above laminated optical film (1), the first optical film is preferably a laminated optical film (2) which is a liquid crystal film or a retardation film.
[0009] In the above laminated optical film (1) or (2), a laminated optical film (3) in which the adhesive layer has a thickness of 0.1 to 10 μm is preferred.
[0010] In any of the above laminated optical films (1) to (3), a laminated optical film (4) is preferred in which a second optical film is further laminated via a pressure-sensitive adhesive layer on the surface of the first optical film opposite to the surface on which the acrylic film is laminated.
[0011] In any one of the above laminated optical films (1) to (4), a laminated optical film (5) is preferred in which the second optical film is a liquid crystal film or a retardation film.
[0012] In any one of the laminated optical films (1) to (5), the adhesive composition contains a polymerizable compound A, and the polymerizable compound A is a urethane (meth)acrylate having a molecular weight of 5,000 or more and having at least two polymerizable groups, and the content of the polymerizable compound A is 4 parts by mass or more and 30 parts by mass or less when the total amount of the polymerizable compounds contained in the adhesive composition is 100 parts by mass. This is a laminated optical film (6) that is preferable.
[0013] In any one of the laminated optical films (1) to (6), the adhesive composition contains a polymerizable compound B, and the polymerizable compound B is a compound having at least two polymerizable groups. When the total amount of the polymerizable compounds contained in the adhesive composition is taken as 100 parts by mass, the content of the polymerizable compound B is preferably 0 part by mass or more and 15 parts by mass or less.
[0014] In any one of the laminated optical films (1) to (7), the adhesive composition contains a polymerizable compound C, and the polymerizable compound C has a logPow of 1.0 or more and 8.0 or less, which represents an octanol / water partition coefficient. When the total amount of the polymerizable compounds contained in the adhesive composition is taken as 100 parts by mass, the content of the polymerizable compound C is 50 parts by mass or more and 95 parts by mass or less. This is a preferred laminated optical film (8).
[0015] In any one of the laminated optical films (1) to (8), the adhesive composition contains a polymerizable compound C, and the polymerizable compound D is a compound having a refractive index of 1.5 or more and 1.7 or less, and when the total amount of the polymerizable compounds contained in the adhesive composition is taken as 100 parts by mass, the content of the polymerizable compound D is 0 part by mass or more and 95 parts by mass or less. This is a laminated optical film (9) that is preferable.
[0016] The present invention also relates to an image display device (10) comprising at least one of the laminated optical films (1) to (9) described above. Effect of the Invention
[0017] As for the acrylic film, since there are almost no functional groups that can contribute to improving the adhesive strength on the film surface, there is a concern that the adhesive strength will be insufficient when the film is made into a laminated optical film, as described above. Here, regarding the acrylic film, there is a method of increasing the adhesive strength between the acrylic film and the adhesive layer by applying an easy-adhesive agent containing an aqueous urethane resin or the like to the acrylic film and forming an easy-adhesion layer. However, due to process constraints, it may be necessary to manufacture a laminated optical film with a structure in which the acrylic film and the adhesive layer are in direct contact with each other without forming an easy-adhesion layer on the acrylic film. In that case, there is a concern that the adhesive strength will be insufficient due to the low interaction between the acrylic film and the adhesive layer.
[0018] By the way, laminated optical films used for in-vehicle applications are required to have excellent appearance characteristics even after a humid durability test in which the film is exposed to an environment of 65°C-95% humidity for 1000 hours. Components that adversely affect appearance characteristics include oxalic acid bright spots that are generated when oxalic acid present in the air forms a salt in a heating process or drying process in which an oven or heating device is used, or in a process in which a film surface is modified, such as corona treatment, plasma treatment, or itro treatment. Conventionally, oxalic acid bright spots have been a problem in adhesive layers that contact polarizers containing metal components such as zinc that cause oxalic acid bright spots. However, as a result of the inventors' investigations, it has been found that even in adhesive layers that do not contact polarizers, specifically adhesive layers that directly contact acrylic films in the present invention, the appearance characteristics are deteriorated due to oxalic acid bright spots that are generated when oxalic acid is mixed in through water vapor or moisture in the air.
[0019] As described above, the laminated optical film having an acrylic film has a unique problem that it is difficult to increase the adhesive strength between the acrylic film and the adhesive layer while suppressing the occurrence of oxalic acid bright spots, because the acrylic film surface has almost no functional groups that can contribute to adhesion, in the case of a structure in which the acrylic film is not treated with an easy adhesive containing an aqueous urethane resin or the like, that is, a structure in which the acrylic film and the adhesive layer are in direct contact with each other. However, in the laminated optical film according to the present invention, even after a humidification durability test, the occurrence of bright spots due to foreign matter is suppressed, and the appearance characteristics are excellent, and the adhesive strength between the laminated optical films is excellent. The reason for such an effect is not clear, but the following reasons are considered.
[0020] The laminated optical film according to the present invention is a laminated optical film in which at least an acrylic film and a first optical film are laminated via an adhesive layer, the adhesive layer being formed of a cured layer of an adhesive composition containing at least a polymerizable compound, and the acrylic film and the adhesive layer are in direct contact with each other. The adhesive composition has a logPow of 1.8 or more and 3.0 or less, which represents an octanol / water partition coefficient calculated by a weighted average of the molar fraction of the polymerizable compound contained in the adhesive composition, and the adhesive layer has an elastic modulus of 1×10 5 Pa or more and 3×10 6 Pa or less. As described above, oxalic acid, which is a component that adversely affects the appearance characteristics, can be mixed into the adhesive layer from the atmosphere through water vapor or moisture in each manufacturing process, but in the present invention, since the above-mentioned (i) configuration is particularly provided, the adhesive layer becomes sufficiently hydrophobic, and the mixing of oxalic acid into the adhesive layer can be suppressed, and the occurrence of oxalic acid bright spots that cause deterioration of the appearance characteristics can be suppressed. On the other hand, when the acrylic film and the adhesive layer are directly contacted with each other, it is difficult to increase the adhesive strength between the acrylic film and the adhesive layer, but since the laminated optical film according to the present invention has the above-mentioned (ii) configuration, the adhesive layer has a sufficiently low elasticity, which causes stress relaxation at the interface between the acrylic film and the adhesive layer, and the adhesion between the two is increased, thereby increasing the adhesive strength. As a result, in the laminated optical film according to the present invention, the occurrence of bright spots due to foreign matter is suppressed even after the humidification durability test, and the laminated optical film has excellent appearance characteristics and excellent adhesive strength between the laminated optical films.
[0021] In particular, when the adhesive layer of the laminated optical film according to the present invention contains at least one of the specific polymerizable compounds A to D, the adhesion to the acrylic film or the effect of suppressing the generation and diffusion of oxalic acid bright spots is further improved. [Brief description of the drawings]
[0022] [Figure 1] 1 is an example of a schematic cross-sectional view of a laminated optical film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] FIG. 1 shows an example of a schematic cross-sectional view of a laminated optical film according to an embodiment of the present invention. In the laminated optical film 10 in this embodiment, an acrylic film 1 and a first optical film 2 are laminated via an adhesive layer 3, and no easy-adhesion layer or the like is interposed between the acrylic film 1 and the adhesive layer 3, and the acrylic film 1 and the adhesive layer 3 are in direct contact with each other. The details of the acrylic film 1, the first optical film 2, and the adhesive layer 3 will be described separately. In the laminated optical film 10 in this embodiment, a triacetyl cellulose film 6, which is a transparent protective film, is laminated via a water-based adhesive layer 7 on the surface of the acrylic film 1 opposite to the surface on which the first optical film 2 is laminated, and a second optical film 4 is further laminated via a pressure-sensitive adhesive layer 5 on the surface of the first optical film 2 opposite to the surface on which the acrylic film 1 is laminated. The details of the pressure-sensitive adhesive layer 5 and the second optical film 4 will be described separately. In this embodiment, the surface of the second optical film 4 opposite to the surface on which the first optical film 2 is laminated is attached to an image display device (not shown in FIG. 1) via a pressure-sensitive adhesive layer 8. Each configuration will be described below.
[0024] <Acrylic film> The acrylic film contains a (meth)acrylic resin. The (meth)acrylic resin film is obtained, for example, by extrusion molding of a molding material containing a resin component mainly containing a (meth)acrylic resin.
[0025] The (meth)acrylic resin preferably has a Tg (glass transition temperature) of 70° C. or higher, more preferably 110° C. or higher, even more preferably 115° C. or higher, and particularly preferably 120° C. or higher. The (meth)acrylic resin film can have excellent durability by containing, as a main component, a (meth)acrylic resin having a Tg (glass transition temperature) of 70° C. or higher. The upper limit of the Tg of the (meth)acrylic resin is not particularly limited, but is preferably 170° C. or lower from the viewpoint of moldability, etc.
[0026] As the (meth)acrylic resin, any appropriate (meth)acrylic resin may be adopted. For example, poly(meth)acrylic acid ester such as polymethyl methacrylate, methyl methacrylate-(meth)acrylic acid copolymer, methyl methacrylate-(meth)acrylic acid ester copolymer, methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymer, methyl (meth)acrylate-styrene copolymer (MS resin, etc.), and polymers having alicyclic hydrocarbon groups (for example, methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.). Preferably, poly(meth)acrylic acid C1-6 alkyl such as polymethyl (meth)acrylate is used. More preferably, methyl methacrylate resins containing methyl methacrylate as the main component (50 to 100% by weight, preferably 70 to 100% by weight) are used.
[0027] In the present invention, the (meth)acrylic resin is preferably a (meth)acrylic resin having a glutaric anhydride structure, a (meth)acrylic resin having a lactone ring structure, or a (meth)acrylic resin having a glutarimide structure, in that they have high heat resistance, high transparency, and high mechanical strength.
[0028] Examples of the (meth)acrylic resin having a glutaric anhydride structure include (meth)acrylic resins having a glutaric anhydride structure described in JP-A Nos. 2006-283013, 2006-335902, and 2006-274118.
[0029] Examples of the (meth)acrylic resin having a lactone ring structure include (meth)acrylic resins having a lactone ring structure described in JP-A Nos. 2000-230016, 2001-151814, 2002-120326, 2002-254544, and 2005-146084.
[0030] Examples of the (meth)acrylic resin having a glutarimide structure include (meth)acrylic resins having a glutarimide structure described in JP-A-2006-309033, JP-A-2006-317560, JP-A-2006-328329, JP-A-2006-328334, JP-A-2006-337491, JP-A-2006-337492, JP-A-2006-337493, JP-A-2006-337569, JP-A-2007-009182, and the like.
[0031] The content of the (meth)acrylic resin in the (meth)acrylic resin film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, further preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. If the content of the (meth)acrylic resin in the (meth)acrylic resin film is less than 50% by weight, the high heat resistance and high transparency inherent to the (meth)acrylic resin may not be fully exhibited.
[0032] The content of the (meth)acrylic resin in the molding material used for molding the (meth)acrylic resin film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, further preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. If the content of the (meth)acrylic resin in the molding material used for molding the (meth)acrylic resin film is less than 50% by weight, the high heat resistance and high transparency inherent to the (meth)acrylic resin may not be fully reflected.
[0033] The (meth)acrylic resin film may contain other thermoplastic resins in addition to the above (meth)acrylic resins. Examples of other thermoplastic resins include olefin polymers such as polyethylene, polypropylene, ethylene-propylene copolymers, and poly(4-methyl-1-pentene); halogenated vinyl polymers such as vinyl chloride, vinylidene chloride, and chlorinated vinyl resins; acrylic polymers such as polymethyl methacrylate; styrene polymers such as polystyrene, styrene-methyl methacrylate copolymers, styrene-acrylonitrile copolymers, and acrylonitrile-butadiene-styrene block copolymers; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyamides such as nylon 6, nylon 66, and nylon 610; polyacetal; polycarbonate; polyphenylene oxide; polyphenylene sulfide; polyether ether ketone; polysulfone; polyether sulfone; polyoxybenzylene; polyamide imide; rubbery polymers such as ABS resins and ASA resins blended with polybutadiene rubber and acrylic rubber.
[0034] The content of other thermoplastic resins in the (meth)acrylic resin film is preferably 0 to 50% by weight, more preferably 0 to 40% by weight, further preferably 0 to 30% by weight, and particularly preferably 0 to 20% by weight.
[0035] The (meth)acrylic resin film may contain additives. Examples of the additives include antioxidants such as hindered phenols, phosphorus, and sulfur; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; ultraviolet absorbers such as phenyl salicylate, (2,2'-hydroxy-5-methylphenyl)benzotriazole, and 2-hydroxybenzophenone; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic and inorganic fillers; resin modifiers; organic and inorganic fillers; plasticizers; lubricants; antistatic agents; flame retardants; retardation reducing agents, and the like.
[0036] The content of the additive in the (meth)acrylic resin film is preferably 0 to 5% by weight, more preferably 0 to 2% by weight, and further preferably 0 to 0.5% by weight.
[0037] The method for producing the (meth)acrylic resin film is not particularly limited, but for example, the (meth)acrylic resin and other polymers, additives, etc. may be thoroughly mixed by any appropriate mixing method to form a thermoplastic resin composition in advance, which may then be molded into a film. Alternatively, the (meth)acrylic resin and other polymers, additives, etc. may each be prepared as separate solutions, which may then be mixed together to form a uniform mixture, which may then be molded into a film.
[0038] To produce the thermoplastic resin composition, the film raw materials are preblended in any suitable mixer such as an omnimixer, and then the resulting mixture is extrusion kneaded. In this case, the mixer used for extrusion kneading is not particularly limited, and any suitable mixer such as an extruder such as a single screw extruder or a twin screw extruder, or a pressure kneader can be used.
[0039] Examples of the film forming method include any appropriate film forming method such as solution casting, melt extrusion, calendaring, compression molding, etc. Among these film forming methods, the solution casting and melt extrusion are preferred.
[0040] Examples of the solvent used in the solution casting method include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as cyclohexane and decalin; esters such as ethyl acetate and butyl acetate; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; alcohols such as methanol, ethanol, isopropanol, butanol, isobutanol, methyl cellosolve, ethyl cellosolve, and butyl cellosolve; ethers such as tetrahydrofuran and dioxane; halogenated hydrocarbons such as dichloromethane, chloroform, and carbon tetrachloride; dimethylformamide; and dimethylsulfoxide. These solvents may be used alone or in combination of two or more.
[0041] Examples of devices for carrying out the solution casting method include a drum type casting machine, a band type casting machine, and a spin coater.
[0042] Examples of the melt extrusion method include a T-die method, an inflation method, etc. The molding temperature is preferably 150 to 350°C, more preferably 200 to 300°C.
[0043] When forming a film by the T-die method, a T-die is attached to the tip of a known single-screw extruder or twin-screw extruder, and the film extruded in a film form is wound up to obtain a roll-shaped film. At this time, it is also possible to perform uniaxial stretching by appropriately adjusting the temperature of the winding roll and applying stretching in the extrusion direction. In addition, it is also possible to perform simultaneous biaxial stretching, sequential biaxial stretching, etc. by stretching the film in a direction perpendicular to the extrusion direction.
[0044] The (meth)acrylic resin film may be either an unstretched film or a stretched film. In the case of a stretched film, it may be either a uniaxially stretched film or a biaxially stretched film. In the case of a biaxially stretched film, it may be either a simultaneous biaxially stretched film or a sequential biaxially stretched film. When the film is biaxially stretched, the mechanical strength is improved, and the film performance is improved. By mixing the (meth)acrylic resin film with another thermoplastic resin, the increase in retardation can be suppressed even when the film is stretched, and optical isotropy can be maintained.
[0045] The stretching temperature is preferably near the glass transition temperature of the thermoplastic resin composition that is the raw material for the film, and specifically, is preferably within the range of (glass transition temperature-30°C) to (glass transition temperature+100°C), and more preferably (glass transition temperature-20°C) to (glass transition temperature+80°C). If the stretching temperature is less than (glass transition temperature-30°C), a sufficient stretch ratio may not be obtained. Conversely, if the stretching temperature exceeds (glass transition temperature+100°C), flow of the resin composition may occur, and stable stretching may not be possible.
[0046] The stretch ratio defined by the area ratio is preferably 1.1 to 25 times, more preferably 1.3 to 10 times. If the stretch ratio is less than 1.1 times, there is a risk that the stretching will not lead to an improvement in toughness. If the stretch ratio is more than 25 times, there is a risk that the effect of increasing the stretch ratio will not be achieved.
[0047] The stretching speed in one direction is preferably 10 to 20,000% / min, more preferably 100 to 10,000% / min. If the stretching speed is less than 10% / min, it takes a long time to obtain a sufficient stretch ratio, and the production cost may increase. If the stretching speed exceeds 20,000% / min, the stretched film may break or the like.
[0048] In order to stabilize the optical isotropy and mechanical properties of the (meth)acrylic resin film, a heat treatment (annealing) or the like can be performed after the stretching treatment. Any appropriate conditions can be adopted as the heat treatment conditions.
[0049] The thickness of the (meth)acrylic resin film is preferably 20 to 60 μm, more preferably 20 to 30 μm. If the thickness is less than 20 μm, not only the strength is reduced, but also the laminated optical film may have a large shrinkage when subjected to a durability test. If the thickness is more than 60 μm, the transparency may be reduced.
[0050] The laminated optical film according to the present invention has a structure in which an acrylic film and a first optical film are laminated via an adhesive layer, and the acrylic film and the adhesive layer are in direct contact with each other. In other words, the acrylic film does not have an easy-adhesion layer. However, the surface of the acrylic film that is in contact with the adhesive layer may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, and itro treatment, and corona treatment is particularly preferable.
[0051] <First optical film> The laminated optical film according to the present invention is formed by laminating at least an acrylic film and a first optical film via an adhesive layer. The first optical film is preferably a liquid crystal film or a retardation film. Examples of the liquid crystal film include an oriented film of a liquid crystal polymer and an oriented layer of a liquid crystal polymer supported by a film. Examples of the retardation film include a retardation film having a front retardation of 40 nm or more and / or a thickness retardation of 80 nm or more. The front retardation is usually controlled to a range of 40 to 200 nm, and the thickness retardation is usually controlled to a range of 80 to 300 nm. Examples of the retardation film include a birefringent film obtained by uniaxially or biaxially stretching a polymer material, an oriented film of a liquid crystal polymer, and an oriented layer of a liquid crystal polymer supported by a film. The thickness of the liquid crystal film and the retardation film is not particularly limited, but is generally about 1 to 150 μm.
[0052] The retardation film may be one represented by the following formulas (1) to (3): 0.70 <Re
[0450] / Re
[0550] <0.97···(1) 1.5×10-3<Δn<6×10-3 (2) 1.13 <NZ<1.50···(3) (wherein Re
[0450] and Re
[0550] are in-plane retardation values of the retardation film measured at 23° C. with light of wavelengths of 450 nm and 550 nm, respectively, Δn is in-plane birefringence, which is nx-ny, when the refractive indices in the slow axis direction and the fast axis direction of the retardation film are nx and ny, respectively, and NZ is the ratio of thickness direction birefringence, nx-nz, to in-plane birefringence, nx-ny, when nz is the refractive index in the thickness direction of the retardation film) may be used.
[0053] <Adhesive layer> The laminated optical film according to the present invention has at least an acrylic film and a first optical film laminated together via an adhesive layer. The acrylic film and the adhesive layer are in direct contact with each other. In other words, no easy-adhesion layer containing a water-based urethane resin or the like is provided between the acrylic film and the adhesive layer.
[0054] In the laminated optical film according to the present invention, the adhesive layer has the following characteristics. (i) The adhesive composition has a logPow, which represents an octanol / water partition coefficient calculated by the weighted average of the molar fractions of the polymerizable compounds contained in the adhesive composition, of 1.8 or more and 3.0 or less. (ii) The elastic modulus of the adhesive layer is 1×10 5 Pa or more and 3×10 6 Pa or less. With regard to (i) above, it is more preferable that the logPow is 2.0 or more and 2.8 or less.
[0055] The octanol / water partition coefficient (logPow) is an index of the lipophilicity of a substance, and refers to the logarithm of the octanol / water partition coefficient. A high logPow value means lipophilicity, that is, hydrophobicity. The logPow value can be measured (flask shaking method described in JIS-Z-7260), but it can also be calculated. In this specification, the logPow value calculated by Chem Draw Ultra manufactured by Cambridge Software is used.
[0056] The logPow of major polymerizable compounds is shown below. Hydroxyethylacrylamide (trade name "HEAA", manufactured by Kohjin Co., Ltd., LogPow; -0.56), diethylacrylamide (trade name "DEAA", manufactured by KJ Chemicals Co., Ltd., LogPow; 1.69), unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone (trade name "Placcel FA1DDM", manufactured by Daicel Corporation, LogPow; 1.06), N-vinylformamide (trade name "Beamset 770", manufactured by Arakawa Chemical Co., Ltd., LogPow; -0.25), acryloylmorpholine (trade name "ACMO ... gPow;-0.20), γ-butyrolactone acrylate (trade name "GBLA", manufactured by Osaka Organic Chemical Industry Co., Ltd., LogPow;0.19), acrylic acid dimer (trade name "β-CEA", manufactured by Daicel Corporation, LogPow;0.2), N-vinylpyrrolidone (trade name "NVP", manufactured by Nippon Shokubai Co., Ltd., LogPow;0.24), acetoacetoxyethyl methacrylate (trade name "AAEM", manufactured by Nippon Synthetic Chemical Industry Co., Ltd., LogPow;0.27), 2-hydroxyethyl acrylate (trade name "HEA", manufactured by Osaka Organic Chemical Industry Co., Ltd., LogPow;0. 28), glycidyl methacrylate (trade name "Light Ester G", Kyoeisha Chemical Co., Ltd., LogPow; 0.57), dimethylacrylamide (trade name "DMAA", Kohjin Co., Ltd., LogPow; 0.58), tetrahydrofurfuryl alcohol acrylic acid polymer ester (trade name "Viscoat #150D", Osaka Organic Chemical Industry Co., Ltd., LogPow; 0.60), 4-hydroxybutyl acrylate (trade name "4-HBA", Osaka Organic Chemical Industry Co., Ltd., LogPow; 0.68), acrylic acid (trade name "Acrylic Acid", Mitsubishi Chemical Corporation, L LogPow;0.69), triethylene glycol diacrylate (trade name "Light Acrylate 3EG-A", Kyoeisha Chemical Co., Ltd., LogPow;0.72), PEG400# diacrylate (trade name "Light Acrylate 9EG-A", Kyoeisha Chemical Co., Ltd., LogPow;-0.1), polypropylene glycol diacrylate (trade name "Aronix M-220", Toagosei Co., Ltd., LogPow;1.68), dicyclopentenyl acrylate (trade name "Fancryl FA-511AS", Hitachi Chemical Co., Ltd., LogPow;2.26), butyl acrylate (trade name "Butyl Acrylate", Mitsubishi Chemical Corporation, LogPow; 2.35), 1,6-hexanediol diacrylate (trade name "Light Acrylate 1.6HX-A", Kyoeisha Chemical Co., Ltd., LogPow; 2.43), dicyclopentanyl acrylate (trade name "Fancryl FA-513AS", Hitachi Chemical Co., Ltd., LogPow; 2.58), dimethylol-tricyclodecane diacrylate (trade name "Light Acrylate DCP-A", Kyoeisha Chemical Co., Ltd., LogPow; 3.05), isobornyl acrylate (trade name "Light Acrylate IB-XA", Kyoeisha Chemical Co., Ltd., LogPow; 3.27), neopentane hydroxypivalate butyl glycol acrylic acid adduct (trade name "Light Acrylate HPP-A", Kyoeisha Chemical Co., Ltd., LogPow; 3.35), 1,9-nonanediol diacrylate (trade name "Light Acrylate 1,9ND-A", Kyoeisha Chemical Co., Ltd., LogPow; 3.68), o-phenylphenol EO modified acrylate (trade name "Fancryl FA-301A", Hitachi Chemical Co., Ltd., LogPow; 3.98), 2-ethylhexyl oxetane (trade name "Aron Oxetane OXT-212", Toagosei Co., Ltd., LogPow; 4.24), bisphenol-A diglycidyl ether (trade name "JER828", Mitsubishi Chemical Co., Ltd., LogPow; 4.76), bisphenol A EO 6 mol modified diacrylate (product name "FA-326A", Hitachi Chemical Co., Ltd., LogPow; 4.84), Bisphenol A EO 4 mol modified diacrylate (product name "FA-324A", Hitachi Chemical Co., Ltd., LogPow; 5.15), Bisphenol A PO 2 mol modified diacrylate (product name "FA-P320A", Hitachi Chemical Co., Ltd., LogPow; 6.10), Bisphenol A PO 3 mol modified diacrylate (product name "FA-P323A", Hitachi Chemical Co., Ltd., LogPow; 6.26), Bisphenol A Examples of such acrylates include PO4-modified diacrylate (product name "FA-P324A", manufactured by Hitachi Chemical Co., Ltd., LogPow; 6.43), lauryl acrylate (product name "Light Acrylate LA", manufactured by Kyoeisha Chemical Co., Ltd., LogPow; 6), and isostearyl acrylate (product name "ISTA", manufactured by Osaka Organic Chemical Industry Co., Ltd., LogPow; 7.46).
[0057] The adhesive layer will be described in detail below. The adhesive layer is formed of a cured product layer of an adhesive composition containing at least a polymerizable compound, and is preferably formed of a cured product layer of an active energy ray curable adhesive composition, such as an electron beam curable, ultraviolet ray curable, or visible light curable adhesive composition. The thickness of the adhesive layer after drying is preferably 0.1 μm to 10 μm, more preferably 0.1 μm to 5 μm, from the viewpoint of improving the appearance characteristics and adhesive strength of the laminated optical film. The active energy ray curable adhesive composition can be divided into a radical polymerization curable adhesive composition and a cationic polymerizable adhesive composition. In the present invention, active energy rays in the wavelength range of 10 nm to less than 380 nm are referred to as ultraviolet rays, and active energy rays in the wavelength range of 380 nm to 800 nm are referred to as visible light.
[0058] The polymerizable compound constituting the radical polymerization curing adhesive composition includes a radical polymerizable compound. The radical polymerizable compound includes a compound having a radical polymerizable functional group of a carbon-carbon double bond such as a (meth)acryloyl group or a vinyl group. These monomer components can be either a monofunctional radical polymerizable compound or a polyfunctional radical polymerizable compound having two or more polymerizable functional groups. These radical polymerizable compounds can be used alone or in combination of two or more. As these radical polymerizable compounds, for example, a compound having a (meth)acryloyl group is suitable. In the present invention, (meth)acryloyl means an acryloyl group and / or a methacryloyl group, and "(meth)" has the same meaning hereinafter.
[0059] Examples of the monofunctional radical polymerizable compound include (meth)acrylamide derivatives having a (meth)acrylamide group. (Meth)acrylamide derivatives are preferred in terms of ensuring adhesion to polarizers and various transparent protective films, and in terms of high polymerization rate and excellent productivity. Specific examples of the (meth)acrylamide derivative include N-alkyl group-containing (meth)acrylamide derivatives such as N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-hexyl(meth)acrylamide; N-hydroxyalkyl group-containing (meth)acrylamide derivatives such as N-methylol(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, and N-methylol-N-propane(meth)acrylamide; N-aminoalkyl group-containing (meth)acrylamide derivatives such as aminomethyl(meth)acrylamide and aminoethyl(meth)acrylamide; N-alkoxy group-containing (meth)acrylamide derivatives such as N-methoxymethylacrylamide and N-ethoxymethylacrylamide; and N-mercaptoalkyl group-containing (meth)acrylamide derivatives such as mercaptomethyl(meth)acrylamide and mercaptoethyl(meth)acrylamide. Examples of heterocycle-containing (meth)acrylamide derivatives in which the nitrogen atom of the (meth)acrylamide group forms a heterocycle include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.
[0060] Among the (meth)acrylamide derivatives, from the viewpoint of adhesion to polarizers and various transparent protective films, N-hydroxyalkyl group-containing (meth)acrylamide derivatives are preferred, and examples of the monofunctional radical polymerizable compound include various (meth)acrylic acid derivatives having a (meth)acryloyloxy group. Specific examples of the acrylate include (meth)acrylic acid (carbon number: 1 to 20) alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate.
[0061] Examples of the (meth)acrylic acid derivatives include cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, and the like. Polycyclic (meth)acrylates such as diethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc.; alkoxy group- or phenoxy group-containing (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, alkylphenoxypolyethylene glycol (meth)acrylate, etc.; and the like.
[0062] In addition, examples of the (meth)acrylic acid derivatives include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. hydroxyl group-containing (meth)acrylates such as [4-(hydroxymethyl)cyclohexyl]methyl acrylate, cyclohexanedimethanol mono(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate glycidyl ether; 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, and 2,2,2-trifluoroethylethyl (meth)acrylate; (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate and other halogen-containing (meth)acrylates; dimethylaminoethyl (meth)acrylate and other alkylaminoalkyl (meth)acrylates; 3-oxetanylmethyl (meth)acrylate, 3-methyl-oxetanylmethyl (meth)acrylate Examples of the methacrylate include oxetane group-containing (meth)acrylates such as 3-ethyl-oxetanylmethyl (meth)acrylate, 3-butyl-oxetanylmethyl (meth)acrylate, and 3-hexyl-oxetanylmethyl (meth)acrylate; (meth)acrylates having a heterocycle such as tetrahydrofurfuryl (meth)acrylate and butyrolactone (meth)acrylate; hydroxypivalic acid neopentyl glycol (meth)acrylic acid adduct; and p-phenylphenol (meth)acrylate.
[0063] Furthermore, examples of the monofunctional radically polymerizable compound include carboxyl group-containing monomers such as (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0064] Examples of the monofunctional radically polymerizable compound include lactam-based vinyl monomers such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone; and vinyl monomers having a nitrogen-containing heterocycle such as vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, and vinylmorpholine.
[0065] In addition, as the monofunctional radical polymerizable compound, a radical polymerizable compound having an active methylene group can be used. The radical polymerizable compound having an active methylene group is a compound having an active double bond group such as a (meth)acrylic group at the end or in the molecule, and having an active methylene group. Examples of the active methylene group include an acetoacetyl group, an alkoxymalonyl group, and a cyanoacetyl group. It is preferable that the active methylene group is an acetoacetyl group. Specific examples of radical polymerizable compounds having an active methylene group include acetoacetoxyalkyl (meth)acrylates such as 2-acetoacetoxyethyl (meth)acrylate, 2-acetoacetoxypropyl (meth)acrylate, and 2-acetoacetoxy-1-methylethyl (meth)acrylate; 2-ethoxymalonyloxyethyl (meth)acrylate, 2-cyanoacetoxyethyl (meth)acrylate, N-(2-cyanoacetoxyethyl)acrylamide, N-(2-propionylacetoxybutyl)acrylamide, N-(4-acetoacetoxymethylbenzyl)acrylamide, and N-(2-acetoacetylaminoethyl)acrylamide. The radical polymerizable compound having an active methylene group is preferably an acetoacetoxyalkyl (meth)acrylate.
[0066] In the present invention, the adhesive composition preferably contains a polymerizable compound B. The polymerizable compound B has a logPow, which represents an octanol / water partition coefficient, of 1.0 or more and 8.0 or less, and when the total amount of the polymerizable compounds contained in the adhesive composition is taken as 100 parts by mass, the content of the polymerizable compound B is preferably 50 parts by mass or more and 90 parts by mass or less, and more preferably 65 parts by mass or more and 90 parts by mass or less. Among the monofunctional radical polymerizable compounds, examples of the polymerizable compound B include the following. (2-Methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate, product name: MEDOL-10, manufacturer: Osaka Organic Chemical Industry Co., Ltd. (logPow: 1.6), benzyl acrylate, product name: Viscoat #160, manufacturer: Osaka Organic Chemical Industry Co., Ltd. (logPow: 2.46), phenoxyethyl acrylate, product name: Viscoat #192HP, manufacturer: Osaka Organic Chemical Industry Co., Ltd. (logPow: 2.52), cyclohexyl Lauryl acrylate, trade name: Viscoat #155, manufacturer: Osaka Organic Chemical Industry Co., Ltd. (logPow: 2.46), lauryl acrylate, trade name: LA, manufacturer: Osaka Organic Chemical Industry Co., Ltd. (logPow: 6), phenoxydiethylene glycol acrylate, trade name: P2H-A, manufacturer: Kyoeisha Chemical Co., Ltd. (logPow: 2.15), phenoxybenzyl acrylate, trade name: POB-A, manufacturer: Kyoeisha Chemical Co., Ltd. (logPow: 3.91). The adhesive composition used in the present invention preferably contains polymerizable compound B, which makes the adhesive layer sufficiently hydrophobic, suppresses the incorporation of oxalic acid into the adhesive layer, and suppresses the occurrence of oxalic acid bright spots that cause deterioration of appearance characteristics.
[0067] Examples of polyfunctional radically polymerizable compounds having two or more polymerizable functional groups include tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol diacrylate, 2-ethyl-2-butylpropanediol di(meth)acrylate, bisphenol A di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, and neopentyl glycol. Examples of the ester compound include esters of (meth)acrylic acid and polyhydric alcohols such as di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, dioxane glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and EO-modified diglycerin tetra(meth)acrylate, and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene. Specific examples include Aronix M-220 (manufactured by Toagosei Co., Ltd.), Light Acrylate 1,9ND-A (manufactured by Kyoeisha Chemical Co., Ltd.), Light Acrylate DGE-4A (manufactured by Kyoeisha Chemical Co., Ltd.), Light Acrylate DCP-A (manufactured by Kyoeisha Chemical Co., Ltd.), SR-531 (manufactured by Sartomer Co., Ltd.), CD-536 (manufactured by Sartomer Co., Ltd.), etc. In addition, various epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, various (meth)acrylate-based monomers, etc. may be mentioned as necessary.
[0068] In the present invention, the adhesive composition preferably contains a polymerizable compound A. The polymerizable compound A is a urethane (meth)acrylate having a molecular weight of 5000 or more and having at least two polymerizable groups. When the total amount of the polymerizable compounds contained in the adhesive composition is taken as 100 parts by mass, the content of the polymerizable compound A is preferably 4 parts by mass or more and 30 parts by mass or less, more preferably 10 parts by mass or more and 20 parts by mass or less. Examples of the polymerizable compound A include Mitsubishi Chemical Corporation's product name "UV3000B" (logPow: 12.8), Daicel Allnex Corporation's product name "EBECRYL4491", Daicel Allnex Corporation's product name "EBECRYL8413", and Sartomer Corporation's product name "CN8888NS". When the adhesive composition used in the present invention contains the polymerizable compound A, the elastic modulus of the adhesive decreases, and adhesion due to stress relaxation becomes possible.
[0069] In the present invention, it is preferable that the adhesive composition contains a polymerizable compound C. The polymerizable compound C is a compound having at least two or more polymerizable groups, and when the total amount of the polymerizable compounds contained in the adhesive composition is 100 parts by mass, the content of the polymerizable compound C is preferably 0 parts by mass or more and 15 parts by mass or less, and more preferably 1 part by mass or more and 10 parts by mass or less. Examples of the polymerizable compound C include the above-mentioned polyfunctional radical polymerizable compounds. By containing the polymerizable compound C in the adhesive composition used in the present invention, it is possible to achieve an elastic modulus that can achieve both adhesion to acrylic film and oxalic acid bright spots.
[0070] In the present invention, the adhesive composition serving as the raw material of the adhesive layer provided in the laminated optical film can contain, in addition to the radically polymerizable compound, an acrylic oligomer obtained by polymerizing a (meth)acrylic monomer. By containing an acrylic oligomer in the adhesive composition, it is possible to reduce the cure shrinkage when the composition is irradiated with active energy rays and cured, and to reduce the interfacial stress between the adhesive layer and the adherend such as a polarizer and an optical film. As a result, it is possible to suppress a decrease in the adhesion between the adhesive layer and the adherend.
[0071] Considering the workability and uniformity during application, it is preferable that the active energy ray curable adhesive has a low viscosity, and therefore it is preferable that the acrylic oligomer obtained by polymerizing the (meth)acrylic monomer also has a low viscosity. As an acrylic oligomer that has a low viscosity and can prevent the curing shrinkage of the adhesive layer, it is preferable that the weight average molecular weight (Mw) is 15000 or less, more preferably 10000 or less, and particularly preferably 5000 or less. On the other hand, in order to sufficiently suppress the curing shrinkage of the cured layer (adhesive layer), the weight average molecular weight (Mw) of the acrylic oligomer is preferably 500 or more, more preferably 1000 or more, and particularly preferably 1500 or more. Specific examples of the (meth)acrylic monomer constituting the acrylic oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, S-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,Examples of the methacrylic acid (1 to 20 carbon atoms) alkyl esters include 2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and N-octadecyl (meth)acrylate. Examples of the methacrylic acid (1 to 20 carbon atoms) alkyl esters include cycloalkyl (meth)acrylates (e.g., cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and the like), aralkyl (meth)acrylates (e.g., benzyl (meth)acrylate, and the like), polycyclic (meth)acrylates (e.g., 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, and the like). (meth)acrylate, etc.), hydroxyl group-containing (meth)acrylic acid esters (e.g., hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethyl-butyl (meth)methacrylate, etc.), alkoxy group- or phenoxy group-containing (meth)acrylic acid esters (2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, etc.), epoxy group-containing (meth)acrylic acid esters (e.g., glycidyl (meth)acrylate, etc.), halogen-containing (meth)acrylic acid esters (e.g., 2,2,2-trifluoroethyl (meth)acrylate, 2,2,Examples of the acrylic oligomer (E) include 2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, etc., and alkylaminoalkyl (meth)acrylates (e.g., dimethylaminoethyl (meth)acrylate, etc.). These (meth)acrylates can be used alone or in combination of two or more. Specific examples of the acrylic oligomer (E) include "ARUFON" manufactured by Toagosei Co., Ltd., "Actflow" manufactured by Soken Chemical & Engineering Co., Ltd., and "JONCRYL" manufactured by BASF Japan Ltd.
[0072] The amount of the acrylic oligomer is preferably 15 parts by weight or less based on 100 parts by weight of the total amount of the monomer components in the adhesive composition. If the content of the acrylic oligomer in the composition is too high, the viscosity of the composition increases, and the surface smoothness after coating is poor, resulting in poor appearance, which is not preferable. On the other hand, in order to sufficiently suppress the curing shrinkage of the adhesive layer, it is preferable that the composition contains 3 parts by weight or more of the acrylic oligomer.
[0073] When a radical polymerizable compound is used, the photopolymerization initiator is appropriately selected depending on the active energy ray. When curing with ultraviolet light or visible light, a photopolymerization initiator that is cleaved by ultraviolet light or visible light is used. Examples of the photopolymerization initiator include benzophenone-based compounds such as benzil, benzophenone, benzoylbenzoic acid, and 3,3'-dimethyl-4-methoxybenzophenone; aromatic ketone compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and α-hydroxycyclohexylphenylketone; acetophenone-based compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1; benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin methyl ether. These include benzoin ether compounds such as benzoin butyl ether and anisoin methyl ether; aromatic ketal compounds such as benzil dimethyl ketal; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenone-1,1-propanedione-2-(o-ethoxycarbonyl)oxime; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone; camphorquinone; halogenated ketones; acylphosphinoxides; and acylphosphonates.
[0074] The amount of the photopolymerization initiator is 20% by weight or less when the total amount of the active energy ray-curable adhesive composition is taken as 100% by weight. The amount of the photopolymerization initiator is preferably 0.01 to 20% by weight, more preferably 0.05 to 10% by weight, and even more preferably 0.1 to 5% by weight.
[0075] When the curable adhesive for laminated optical films of the present invention is used as a visible light curable type containing a radical polymerizable compound as a curable component, it is preferable to use a photopolymerization initiator that is highly sensitive to light of 380 nm or more. Photopolymerization initiators that are highly sensitive to light of 380 nm or more will be described later.
[0076] It is also preferable to add a polymerization initiator aid as necessary. Examples of the polymerization initiator aid include triethylamine, diethylamine, N-methyldiethanolamine, ethanolamine, 4-dimethylaminobenzoic acid, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, and isoamyl 4-dimethylaminobenzoate, with ethyl 4-dimethylaminobenzoate being particularly preferable. When using a polymerization initiator aid, the amount added is usually 0 to 5 parts by weight, preferably 0 to 4 parts by weight, and most preferably 0 to 3 parts by weight, based on 100 parts by weight of the total amount of the curable components.
[0077] Also, a known photopolymerization initiator can be used in combination as necessary. Since the transparent protective film having UV absorbing ability does not transmit light of 380 nm or less, it is preferable to use a photopolymerization initiator that is highly sensitive to light of 380 nm or more as the photopolymerization initiator. Specifically, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, etc. can be mentioned.
[0078] In particular, as the photopolymerization initiator, in addition to the photopolymerization initiator of general formula (1), a compound represented by the following general formula (2):
[0079] [ka] (In the formula, R 3 , R 4 and R 5 represents -H, -CH3, -CH2CH3, -iPr or Cl, and R 3 , R 4 and R 5 (which may be the same or different) is preferably used. As the compound represented by the general formula (2), commercially available products such as 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (trade name: Omnirad819, manufacturer: IGM Resins BV) and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad907, manufacturer: IGM Resins BV) can be suitably used. In addition, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (trade name: Omnirad369, manufacturer: IGM Resins BV) and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad379, manufacturer: IGM Resins BV) are preferred due to their high sensitivity.
[0080] In the present invention, among the above photopolymerization initiators, it is preferable to use a hydroxyl group-containing photopolymerization initiator. When the active energy ray-curable adhesive composition contains a hydroxyl group-containing photopolymerization initiator as a polymerization initiator, the solubility in the adhesive layer having a high concentration of the A component on the polarizer side is increased, and the curability of the adhesive layer is improved. Examples of photopolymerization initiators having a hydroxyl group include 2-methyl-2-hydroxypropiophenone (trade name "DAROCUR1173", manufactured by BASF), 1-hydroxycyclohexyl phenyl ketone (trade name "IRGACURE184", manufactured by BASF), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (trade name "IRGACURE2959", manufactured by BASF), and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one (trade name "IRGACURE127", manufactured by BASF). In particular, 1-hydroxycyclohexyl phenyl ketone is more preferable because it has excellent solubility in the adhesive layer having a high concentration of component A.
[0081] In the present invention, a cationic polymerizable adhesive composition may be used as an adhesive composition that is a raw material for the adhesive layer provided in the laminated optical film. The cationic polymerizable compounds used in the cationic polymerizable adhesive composition are classified into monofunctional cationic polymerizable compounds having one cationic polymerizable functional group in the molecule and polyfunctional cationic polymerizable compounds having two or more cationic polymerizable functional groups in the molecule. Since the liquid viscosity of the monofunctional cationic polymerizable compound is relatively low, the liquid viscosity of the resin composition can be reduced by including it in the resin composition. In addition, the monofunctional cationic polymerizable compound often has a functional group that exhibits various functions, and the cationic polymerizable adhesive composition and / or the cured product of the cationic polymerizable adhesive composition can exhibit various functions by including it in the cationic polymerizable adhesive composition. The polyfunctional cationic polymerizable compound can three-dimensionally crosslink the cured product of the cationic polymerizable adhesive composition, so it is preferable to include it in the cationic polymerizable adhesive composition. The ratio of the monofunctional cationic polymerizable compound to the polyfunctional cationic polymerizable compound is preferably in the range of 10 parts by weight to 1000 parts by weight of the polyfunctional cationic polymerizable compound mixed with 100 parts by weight of the monofunctional cationic polymerizable compound. Examples of the cationic polymerizable functional group include an epoxy group, an oxetanyl group, and a vinyl ether group. Examples of the compound having an epoxy group include an aliphatic epoxy compound, an alicyclic epoxy compound, and an aromatic epoxy compound. It is particularly preferable that the cationic polymerizable adhesive composition of the present invention contains an alicyclic epoxy compound because of its excellent curability and adhesiveness. Examples of alicyclic epoxy compounds include 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, caprolactone-modified 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, trimethylcaprolactone-modified 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and valerolactone-modified 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate. Specific examples include Celloxide 2021, Celloxide 2021A, Celloxide 2021P, Celloxide 2081, Celloxide 2083, Celloxide 2085 (all manufactured by Daicel Chemical Industries, Ltd.), Cyracure UVR-6105, Cyracure UVR-6107, Cyracure 30, and R-6110 (all manufactured by Dow Chemical Japan, Ltd.).Compounds having an oxetanyl group are preferably contained because they improve the curing property of the cationic polymerizable adhesive composition and reduce the liquid viscosity of the composition. Examples of compounds having an oxetanyl group include 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, 3-ethyl-3-(phenoxymethyl)oxetane, di[(3-ethyl-3-oxetanyl)methyl]ether, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and phenol novolac oxetane, and ARON OXETANE OXT-101, ARON OXETANE OXT-121, ARON OXETANE OXT-211, ARON OXETANE OXT-221, and ARON OXETANE OXT-212 (all manufactured by Toagosei Co., Ltd.) are commercially available. The compound having a vinyl ether group is preferably contained since it has the effect of improving the curing property of the cationic polymerizable adhesive composition and reducing the liquid viscosity of the composition. Examples of the compound having a vinyl ether group include 2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, triethylene glycol divinyl ether, cyclohexane dimethanol divinyl ether, cyclohexane dimethanol monovinyl ether, tricyclodecane vinyl ether, cyclohexyl vinyl ether, methoxyethyl vinyl ether, ethoxyethyl vinyl ether, and pentaerythritol tetravinyl ether.
[0082] The cationic polymerizable adhesive composition contains at least one compound selected from the compounds having an epoxy group, the compounds having an oxetanyl group, and the compounds having a vinyl ether group described above as a curable component, and since all of these are cured by cationic polymerization, a photocationic polymerization initiator is blended. This photocationic polymerization initiator generates cationic species or Lewis acid by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, and initiates the polymerization reaction of the epoxy group or the oxetanyl group. As the photocationic polymerization initiator, a photoacid generator described later is preferably used. In addition, when the cationic polymerizable adhesive composition is used as a visible light curable composition, it is preferable to use a photocationic polymerization initiator that is highly sensitive to light of 380 nm or more, but since photocationic polymerization initiators are generally compounds that show maximum absorption in the vicinity of 300 nm or shorter wavelength range, by blending a photosensitizer that shows maximum absorption in light of a longer wavelength range, specifically, a wavelength longer than 380 nm, it is possible to promote the generation of cationic species or acid from the photocationic polymerization initiator by responding to light of this vicinity wavelength. Examples of photosensitizers include anthracene compounds, pyrene compounds, carbonyl compounds, organic sulfur compounds, persulfides, redox compounds, azo and diazo compounds, halogen compounds, photoreducible dyes, etc., and these may be used in combination of two or more. In particular, anthracene compounds are preferred because they have excellent photosensitizing effects, and specific examples include Anthracure UVS-1331 and Anthracure UVS-1221 (manufactured by Kawasaki Chemical Industries, Ltd.). The content of the photosensitizer is preferably 0.1% by weight to 5% by weight, more preferably 0.5% by weight to 3% by weight.
[0083] The laminated optical film 10 shown in Figure 1 further comprises a triacetyl cellulose film 6, which is a transparent protective film, laminated via a water-based adhesive layer 7 on the surface of the acrylic film 1 opposite to the surface on which the first optical film 2 is laminated, and a second optical film 4 laminated via a pressure-sensitive adhesive layer 5 on the surface of the first optical film 2 opposite to the surface on which the acrylic film 1 is laminated.
[0084] <Adhesive layer> The adhesive for forming the adhesive layer is not particularly limited, and can be appropriately selected and used, for example, those having a base polymer such as an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, etc. In particular, those having excellent optical transparency, exhibiting adhesive properties such as appropriate wettability, cohesiveness, and adhesiveness, and having excellent weather resistance, heat resistance, etc., such as acrylic adhesives, can be preferably used.
[0085] A separator is temporarily attached to cover the exposed surface of the adhesive layer for the purpose of preventing contamination until it is put into practical use. This prevents contact with the adhesive layer in normal handling conditions. As the separator, except for the above thickness conditions, a suitable thin sheet such as a plastic film, a rubber sheet, paper, cloth, nonwoven fabric, net, foam sheet, metal foil, or a laminate thereof, which is coated with a suitable release agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide-based, as necessary, or the like, may be used as appropriate according to conventional methods.
[0086] <Second optical film> In the present invention, the second optical film is preferably a liquid crystal film or a retardation film, and the same liquid crystal film and retardation film as those exemplified for the first optical film can be suitably used.
[0087] The laminated optical film according to the present invention may include the following optical films in addition to the acrylic film, the first optical film and the second optical film.
[0088] The laminated optical film according to the present invention may include a polarizer as another optical film. As a material for the polyvinyl alcohol-based film applied to the polarizer, polyvinyl alcohol or a derivative thereof is used. Examples of the polyvinyl alcohol derivative include polyvinyl formal, polyvinyl acetal, etc., as well as those modified with olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, their alkyl esters, acrylamide, etc. Polyvinyl alcohol having a degree of polymerization of about 1000 to 10000 and a degree of saponification of about 80 to 100 mol % is generally used.
[0089] The polyvinyl alcohol-based film may contain additives such as a plasticizer. Examples of the plasticizer include polyols and their condensates, such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol. The amount of the plasticizer used is not particularly limited, but is preferably 20% by weight or less in the polyvinyl alcohol-based film.
[0090] In producing a polarizer, a dyeing step in which the polyvinyl alcohol-based film is dyed with iodine and a stretching step in which the polyvinyl alcohol-based film is stretched in at least one direction are performed. In general, a method is adopted in which the polyvinyl alcohol-based film is subjected to a series of steps including swelling, dyeing, crosslinking, stretching, water washing, and drying steps.
[0091] The swelling step is carried out, for example, by immersing the polyvinyl alcohol film in a swelling bath (water bath). This treatment cleans the surface of the polyvinyl alcohol film from dirt and antiblocking agents, and swells the polyvinyl alcohol film to prevent non-uniformity such as uneven dyeing. Glycerin, potassium iodide, etc. may be appropriately added to the swelling bath. The temperature of the swelling bath is usually about 20 to 60°C, and the immersion time in the swelling bath is usually about 0.1 to 10 minutes.
[0092] The dyeing step is carried out, for example, by immersing the polyvinyl alcohol film in an iodine solution. The iodine solution is usually an aqueous iodine solution, containing iodine and potassium iodide as a dissolving agent. The iodine concentration is usually about 0.01 to 1 wt%, preferably 0.02 to 0.5 wt%. The potassium iodide concentration is usually about 0.01 to 10 wt%, preferably 0.02 to 8 wt%.
[0093] In the iodine dyeing step, the temperature of the iodine solution is usually about 20 to 50° C., preferably 25 to 40° C. The immersion time is usually about 10 to 300 seconds, preferably 20 to 240 seconds. In the iodine dyeing treatment, it is preferable to adjust conditions such as the concentration of the iodine solution, the immersion temperature of the polyvinyl alcohol film in the iodine solution, and the immersion time so that the iodine content and potassium content in the polyvinyl alcohol film are within the above-mentioned ranges.
[0094] The crosslinking step is carried out, for example, by immersing a polyvinyl alcohol film dyed with iodine in a treatment bath containing a crosslinking agent. Any appropriate crosslinking agent is used as the crosslinking agent. Specific examples of the crosslinking agent include boron compounds such as boric acid and borax, glyoxal, and glutaraldehyde. These are used alone or in combination. Water is generally used as a solvent for the crosslinking bath solution, but an appropriate amount of an organic solvent compatible with water may be added. The crosslinking agent is usually used in a ratio of 1 to 10 parts by weight with respect to 100 parts by weight of the solvent. It is desirable that the crosslinking bath solution further contains an auxiliary such as an iodide. The concentration of the auxiliary is preferably 0.05 to 15% by weight, more preferably 0.5 to 8% by weight. The temperature of the crosslinking bath is usually about 20 to 70°C, preferably 40 to 60°C. The immersion time in the crosslinking bath is usually about 1 second to 15 minutes, preferably 5 seconds to 10 minutes.
[0095] The stretching step is a step in which a polyvinyl alcohol-based film is stretched in at least one direction. In general, the polyvinyl alcohol-based film is uniaxially stretched in the conveying direction (longitudinal direction). The stretching method is not particularly limited, and either a wet stretching method or a dry stretching method can be adopted. When the wet stretching method is adopted, the polyvinyl alcohol-based film is stretched to a predetermined ratio in a treatment bath. As a solution for the stretching bath, a solution in which a compound required for various treatments is added to a solvent such as water or an organic solvent (e.g., ethanol) is preferably used. Examples of the dry stretching method include a roll-to-roll stretching method, a heated roll stretching method, and a compression stretching method. In the production of a polarizer, the stretching step may be performed at any stage. Specifically, it may be performed simultaneously with swelling, dyeing, and crosslinking, or may be performed before or after each of these steps. In addition, the stretching may be performed in multiple stages. The cumulative stretching ratio of the polyvinyl alcohol-based film is usually 5 times or more, and preferably about 5 to 7 times.
[0096] In the present invention, the polarizer preferably contains a metal component capable of becoming a divalent metal cation in water, more preferably contains magnesium, calcium, copper or zinc, and particularly preferably contains zinc. When the polarizer contains zinc, there is a tendency that the decrease in transmittance and the deterioration in hue of the laminated optical film after a heating test are suppressed. When the polarizer contains zinc, the content of zinc in the polarizer is preferably 0.002 to 2 wt%, more preferably 0.01 to 1 wt%.
[0097] In the present invention, the polarizer preferably contains sulfate ions. When the polarizer contains sulfate ions, the decrease in the transmittance of the laminated optical film after a heating test tends to be suppressed. When the polarizer contains sulfate ions, the content of sulfate ions in the polarizer is preferably 0.02 to 0.45% by weight, more preferably 0.05 to 0.35% by weight, and further preferably 0.1 to 0.25% by weight. The content of sulfate ions in the polarizer is calculated from the sulfur atom content.
[0098] In order to incorporate zinc into the polarizer, it is preferable to carry out a zinc impregnation treatment in the manufacturing process of the polarizer. In order to incorporate sulfate ions into the polarizer, it is preferable to carry out a sulfate ion treatment in the manufacturing process of the polarizer.
[0099] The zinc impregnation treatment is carried out, for example, by immersing the polyvinyl alcohol film in a zinc salt solution. As the zinc salt, an inorganic salt compound such as an aqueous solution of zinc halide such as zinc chloride or zinc iodide, zinc sulfate, or zinc acetate is suitable. In addition, various zinc complex compounds may be used for the zinc impregnation treatment. In addition, it is preferable to use an aqueous solution of potassium ion and iodine ion by potassium iodide or the like as the zinc salt solution, since it is easy to impregnate the zinc ion. The concentration of potassium iodide in the zinc salt solution is about 0.5 to 10% by weight, and more preferably 1 to 8% by weight.
[0100] The sulfate ion treatment is carried out, for example, by immersing the polyvinyl alcohol-based film in an aqueous solution containing a metal sulfate. The metal sulfate is preferably one that is easily separated into sulfate ions and metal ions in the treatment solution and is easily introduced in the form of ions into the polyvinyl alcohol-based film. For example, metals that form metal sulfate include alkali metals such as sodium and potassium; alkaline earth metals such as magnesium and calcium; and transition metals such as cobalt, nickel, zinc, chromium, aluminum, copper, manganese, and iron.
[0101] In the manufacture of a polarizer, the zinc impregnation treatment and the sulfate ion treatment may be performed at any stage. That is, the zinc impregnation treatment and the sulfate ion treatment may be performed before or after the dyeing step. The zinc impregnation treatment and the sulfate ion treatment may be performed simultaneously. In the present invention, it is preferable to use zinc sulfate as the zinc salt and the metal sulfate salt, and to simultaneously perform the zinc impregnation treatment and the sulfate ion treatment by immersing the polyvinyl alcohol film in a treatment bath containing zinc sulfate. In addition, the zinc salt and the metal sulfate salt may be coexisted in the dyeing solution, and the zinc impregnation treatment and / or the sulfate ion treatment may be performed simultaneously with the dyeing step. The zinc impregnation treatment and the sulfate ion treatment may be performed simultaneously with the stretching.
[0102] In the zinc impregnation treatment and sulfate ion treatment, the zinc content and sulfate ion content in the polarizer are adjusted by adjusting the conditions such as the concentration of the zinc salt solution and the metal sulfate solution, the immersion temperature of the polyvinyl alcohol film in the treatment bath, and the immersion time. In the zinc impregnation treatment and sulfate ion treatment, the temperature of the zinc salt solution and the metal sulfate solution is usually about 15 to 85°C, preferably 25 to 70°C. The immersion time is usually about 1 to 120 seconds, preferably 3 to 90 seconds. The concentration of the zinc salt solution and the metal sulfate solution varies depending on the type of zinc salt and metal sulfate, but is usually about 0.5 to 20% by weight, preferably 1 to 10% by weight, and more preferably 2 to 7% by weight. By setting the zinc salt concentration and the metal sulfate concentration in the above ranges, the zinc content and sulfate ion content in the polarizer can be set within the above preferred ranges.
[0103] The polyvinyl alcohol film (stretched film) that has been subjected to the above-mentioned treatments is subjected to a water washing step and a drying step according to a conventional method.
[0104] The water washing step is usually carried out by immersing the polyvinyl alcohol film in a water washing bath. The water washing bath may be pure water or an aqueous solution of an iodide (e.g., potassium iodide, sodium iodide, etc.). The concentration of the aqueous iodide solution is preferably 0.1 to 10% by weight. An auxiliary such as zinc sulfate or zinc chloride may be added to the aqueous iodide solution.
[0105] The washing temperature is usually in the range of 5 to 50°C, preferably 10 to 45°C, and more preferably 15 to 40°C. The immersion time is usually about 10 to 300 seconds, and preferably 20 to 240 seconds. The washing step may be carried out only once, or may be carried out multiple times as necessary. When the washing step is carried out multiple times, the type and concentration of additives contained in the washing bath used for each treatment are appropriately adjusted.
[0106] The drying process of the polyvinyl alcohol-based film is carried out by any appropriate method (for example, natural drying, air drying, heat drying). The thickness of the polarizer after the drying process is preferably 3 to 20 μm.
[0107] In the present invention, the obtained polarizer may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, and itro treatment, and corona treatment is particularly preferable. By performing corona treatment, reactive functional groups such as carbonyl groups and amino groups are generated on the polarizer surface, and the adhesion to the durability improving layer is improved. In addition, the ashing effect removes foreign matter on the surface and reduces surface unevenness, making it possible to prepare a laminated optical film with excellent appearance characteristics.
[0108] The laminated optical film according to the present invention may include a transparent protective film as another optical film. As a material for forming the transparent protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The transparent protective film may contain one or more types of any suitable additives. Examples of additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, coloring inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, colorants, etc. The content of the thermoplastic resin in the transparent protective film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, further preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. If the content of the thermoplastic resin in the transparent protective film is 50% by weight or less, the inherent high transparency of the thermoplastic resin may not be fully exhibited.
[0109] The material for forming the transparent protective film is preferably one having excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc., and in particular, a moisture permeability of 150 g / m 2 / 24h or less is more preferable, and 140g / m 2 / 24h or less is particularly preferred, and 120g / m 2 / 24h or less is even more preferable.
[0110] The transparent protective film may be provided with a functional layer such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, an anti-glare layer, etc. The functional layer such as the hard coat layer, the anti-reflection layer, the anti-sticking layer, the diffusion layer, the anti-glare layer, etc. may be provided on the transparent protective film itself, or may be provided separately from the transparent protective film.
[0111] The thickness of the transparent protective film can be appropriately determined, but is generally about 1 to 500 μm, preferably 1 to 300 μm, more preferably 5 to 200 μm, further preferably 10 to 200 μm, and more preferably 20 to 80 μm, from the viewpoints of workability such as strength and handleability, thinness, etc.
[0112] The laminated optical film according to the present invention can be produced, for example, by the following production method. A method for producing a laminated optical film in which at least an acrylic film and a first optical film are laminated via an adhesive layer, comprising the steps of: the adhesive layer is formed of a cured layer of an adhesive composition containing at least a polymerizable compound, a coating step of coating the adhesive composition on at least one of the acrylic film and the first optical film; A method for producing a laminated optical film, comprising: a lamination step of laminating the acrylic film and the first optical film together so that the acrylic film and the adhesive layer are in direct contact with each other; and an adhesion step of adhering the acrylic film and the first optical film together via an adhesive layer formed by irradiating the acrylic film side or the first optical film side with active energy rays to cure at least the adhesive composition. Each step will be described below.
[0113] (Coating process) The method of applying the adhesive composition to at least one of the acrylic film and the first optical film is appropriately selected depending on the viscosity of the composition and the desired thickness, and examples thereof include a reverse coater, a gravure coater (direct, reverse, or offset), a bar reverse coater, a roll coater, a die coater, a bar coater, and a rod coater. The viscosity of the adhesion-promoting composition and the adhesive composition is preferably 0.1 to 200 mPa·s, more preferably 1 to 100 mPa·s, and most preferably 5 to 50 mPa·s. If the viscosity of the composition is high, the surface smoothness after application is poor, which is not preferable because it causes poor appearance. For this reason, each composition can be heated or cooled to adjust the viscosity to a preferred range and then applied.
[0114] (Lamination process) The acrylic film and the first optical film are bonded together so that the acrylic film and the adhesive layer are in direct contact with each other. When the adhesive composition is applied to the acrylic film in the coating process, the adhesive composition is directly applied to the acrylic film without coating an easy-to-adhere adhesive containing an aqueous urethane resin or the like on the acrylic film, and the acrylic film is bonded to the first optical film in that state. Also, when the adhesive composition is applied to the first optical film in the coating process, the adhesive composition-coated surface of the first optical film and the acrylic film are directly bonded together without using an easy-to-adhere adhesive or the like. When the acrylic film and the first optical film are bonded together via the adhesive composition, they are bonded together using a roll laminator or the like.
[0115] (Adhesion process) The acrylic film and the first optical film are bonded via an adhesive layer formed by curing at least the adhesive composition by irradiating active energy rays from the acrylic film side or the first optical film side. The irradiation direction of the active energy rays (electron beams, ultraviolet rays, visible light, etc.) can be any appropriate direction.
[0116] When irradiating with electron beams, any suitable irradiation conditions can be adopted as long as the conditions are such that at least the adhesive composition can be cured. For example, the acceleration voltage of the electron beam irradiation is preferably 5 kV to 300 kV, more preferably 10 kV to 250 kV. If the acceleration voltage is less than 5 kV, the electron beam may not reach the adhesive, resulting in insufficient curing, and if the acceleration voltage is more than 300 kV, the penetration force through the sample is too strong, resulting in damage to the first optical film and the second optical film. The irradiation dose is 5 to 100 kGy, more preferably 10 to 75 kGy. If the irradiation dose is less than 5 kGy, the adhesive may not be cured sufficiently, and if it exceeds 100 kGy, the first optical film and the second optical film may be damaged, resulting in a decrease in mechanical strength and yellowing, and the desired optical properties may not be obtained.
[0117] Electron beam irradiation is usually performed in an inert gas, but may be performed in air or with a small amount of oxygen introduced if necessary. Although it depends on the materials of the first and second optical films, by appropriately introducing oxygen, oxygen inhibition is intentionally generated on the first and second optical film surfaces that are first hit by the electron beam, which makes it possible to prevent damage to the first and second optical films and to efficiently irradiate only the adhesive with the electron beam.
[0118] When manufacturing the laminated optical film according to the present invention, it is preferable to use active energy rays including visible light in the wavelength range of 380nm to 450nm, particularly active energy rays having the largest amount of visible light in the wavelength range of 380nm to 450nm. When using ultraviolet rays and visible light, if a second optical film having ultraviolet absorbing ability is used, such as an ultraviolet non-transmitting transparent protective film, light with a wavelength shorter than about 380nm is absorbed, so that light with a wavelength shorter than 380nm does not reach the adhesive composition and does not contribute to the polymerization reaction. Furthermore, light with a wavelength shorter than 380nm absorbed by the first optical film and the second optical film is converted into heat, and the first optical film and the second optical film themselves generate heat, causing defects such as curling and wrinkling of the laminated optical film. Therefore, when ultraviolet rays and visible light are employed in the present invention, it is preferable to use a device that does not emit light with a wavelength shorter than 380 nm as an active energy ray generator, and more specifically, the ratio of the integrated illuminance in the wavelength range of 380 to 440 nm to the integrated illuminance in the wavelength range of 250 to 370 nm is preferably 100:0 to 100:50, more preferably 100:0 to 100:40. When producing the laminated optical film according to the present invention, the active energy ray is preferably a gallium-encapsulated metal halide lamp or an LED light source that emits light in the wavelength range of 380 to 440 nm. Alternatively, a light source containing ultraviolet rays and visible light such as a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, an incandescent lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a metal halide lamp, a fluorescent lamp, a tungsten lamp, a gallium lamp, an excimer laser, or sunlight can be used, and a bandpass filter can be used to block ultraviolet rays with a wavelength shorter than 380 nm. In order to prevent curling of the laminated optical film while improving the adhesive performance of the adhesive layer between the first optical film and the second optical film, it is preferable to use active energy rays obtained by using a gallium-encapsulated metal halide lamp and passing through a bandpass filter capable of blocking light with wavelengths shorter than 380 nm, or active energy rays with a wavelength of 405 nm obtained by using an LED light source.
[0119] When the laminated optical film according to the present invention is produced on a continuous line, the line speed depends on the curing time of the adhesive composition, but is preferably 1 to 500 m / min, more preferably 5 to 300 m / min, and even more preferably 10 to 100 m / min. If the line speed is too slow, the productivity is poor, or the damage to the first optical film or the second optical film is too great, and a laminated optical film that can withstand a durability test or the like cannot be produced. If the line speed is too high, the adhesive composition is insufficiently cured, and the desired adhesiveness may not be obtained.
[0120] (Laminated optical film) The laminated optical film according to the present invention can be preferably used for forming various image display devices such as liquid crystal display devices. The formation of the liquid crystal display device can be carried out in accordance with the conventional method. That is, a liquid crystal display device is generally formed by appropriately assembling components such as a liquid crystal cell, a polarizing film or an optical film, and an optional lighting system, and incorporating a driving circuit, but in the present invention, there is no particular limitation except that the laminated optical film according to the present invention is used, and the method can be carried out in accordance with the conventional method. As for the liquid crystal cell, any type such as a TN type, STN type, or π type can be used.
[0121] It is possible to form a suitable liquid crystal display device, such as a liquid crystal display device in which an optical laminate is arranged on one or both sides of a liquid crystal cell, or a display device using a backlight or a reflector in the illumination system. In this case, the optical laminate according to the present invention can be installed on one or both sides of a liquid crystal cell. When optical laminates are provided on both sides, they may be the same or different. Furthermore, when forming a liquid crystal display device, suitable components such as a diffusion plate, an anti-glare layer, an anti-reflection film, a protective plate, a prism array, a lens array sheet, a light diffusion plate, a backlight, etc. can be arranged in one or more layers at suitable positions. EXAMPLES
[0122] Examples of the present invention are described below, but the embodiments of the present invention are not limited thereto.
[0123] (Method for measuring storage modulus of adhesive layer) The storage modulus of the adhesive layer was measured using a dynamic viscoelasticity measuring device Dva225 manufactured by IT Measurement & Control Co., Ltd. under the following measurement conditions. Sample size: width 50mm, length 30mm, Clamping distance 20mm, Measurement mode: tension, frequency: 1Hz, Heating rate: 5℃ / min Dynamic viscoelasticity was measured, and the measured value at 25°C was taken as storage modulus.
[0124] <Acrylic film> The acrylic film used was "RX420" manufactured by Nippon Shokubai Co., Ltd.
[0125] <Liquid crystal film> The following λ / 2 retardation film was obtained as a liquid crystal film based on the following photopolymerizable liquid crystal composition.
[0126] <Photopolymerizable liquid crystal composition> A photopolymerizable liquid crystal compound exhibiting a nematic liquid crystal phase (BASF's "Paliocolor LC242") was dissolved in cyclopentanone to prepare a solution with a solid content of 30% by weight. A surfactant (BYK-360, BYK-Chemie) and a photopolymerization initiator (IGM Resins' "Omnirad907") were added to this solution to prepare a liquid crystal composition solution. The amounts of the leveling agent and polymerization initiator added were 0.01 parts by weight and 3 parts by weight, respectively, relative to 100 parts by weight of the photopolymerizable liquid crystal compound.
[0127] <λ / 2 phase difference film> A biaxially stretched norbornene film (ZEONORFILM manufactured by ZEON Corporation, thickness: 33 μm, front retardation: 135 nm) was used as a substrate, and the above liquid crystal composition was applied to the substrate with a bar coater so that the phase difference was λ / 2, and the liquid crystal was aligned by heating at 100° C. for 3 minutes. After cooling to room temperature, the liquid crystal was aligned in a nitrogen atmosphere with an accumulated light amount of 400 mJ / cm 2 . 2The laminate was then irradiated with ultraviolet light of 1000 ohms for photocuring to obtain a laminate provided with a homogeneously aligned liquid crystal layer.
[0128] <Preparation of polarizing film> A polyvinyl alcohol film with an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol%, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was stretched 2.2 times in the conveying direction while swelling by immersing in a swelling bath (water bath) at 30° C. between rolls with different peripheral speed ratios (swelling step), and then stretched 3.3 times in the conveying direction based on the original polyvinyl alcohol film (polyvinyl alcohol film not stretched at all in the conveying direction) while dyeing by immersing in a dyeing bath (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at 30° C. for 30 seconds while adjusting the iodine concentration so that the polarizing film has a predetermined transmittance (dyeing step). Next, the dyed polyvinyl alcohol film was immersed in a 40°C crosslinking bath (aqueous solution with a boric acid concentration of 3.5% by weight, a potassium iodide concentration of 3.0% by weight, and a zinc sulfate concentration of 3.6% by weight) for 28 seconds, and stretched to 3.6 times the original polyvinyl alcohol film in the conveying direction (crosslinking step). Furthermore, the obtained polyvinyl alcohol film was immersed in a 64°C stretching bath (aqueous solution with a boric acid concentration of 4.8% by weight, a potassium iodide concentration of 5.0% by weight, and a zinc sulfate concentration of 5.0% by weight) for 60 seconds, and stretched to 6.0 times the original polyvinyl alcohol film in the conveying direction (stretching step), and then immersed in a 29°C washing bath (potassium iodide concentration of 2.3% by weight) for 10 seconds (washing step). The washed polyvinyl alcohol film was dried at 40°C for 30 seconds to prepare a polarizing film. The polarizing film had a thickness of 18 μm.
[0129] <Preparation of polarizing film> As the adhesive, an aqueous solution containing an acetoacetyl group-containing polyvinyl alcohol resin (average degree of polymerization 1,200, degree of saponification 98.5 mol%, degree of acetoacetylation 5 mol%) and methylol melamine in a weight ratio of 3:1 was used. Using this adhesive, a 39 μm-thick triacetyl cellulose film (manufactured by Konica Minolta, product name "KC4UY") having a hard coat layer as a transparent protective film was laminated on one side of the polarizing film obtained above via an aqueous adhesive layer 7, and a 30 μm-thick acrylic film (RX420) was laminated on the other side via an aqueous adhesive layer 3 using a roll laminator, and then the resulting film was heated and dried in an oven (temperature 60° C., time 4 minutes) to produce polarizing film 1.
[0130] <Active energy rays> Visible light (gallium-filled metal halide lamp) as active energy rays Irradiation device: Light HAMMER10 manufactured by Fusion UV Systems, Inc. Bulb: V bulb Peak illuminance: 1600mW / cm 2 , cumulative irradiation dose 1000mJ / cm 2 The illuminance of visible light was measured using a Sola-Check system manufactured by Solatell.
[0131] Examples 1 to 4 and Comparative Examples 1 to 2 The adhesive composition adjusted to the blending amount shown in Table 1 was applied to the acrylic film surface of the polarizing film and the homogeneously oriented liquid crystal layer surface of the liquid crystal film (a laminate of a biaxially stretched norbornene-based film and a homogeneously oriented liquid crystal layer) using an MCD coater (manufactured by Fuji Machine Co., Ltd.) (cell shape: honeycomb, gravure roll line count: 700 rolls / inch, rotation speed 140% / to line speed) on the polarizing film 1 so that the adhesive layer had a thickness of 2 μm, and then laminated with a roll machine. Thereafter, the adhesive composition was cured by irradiating the above-mentioned visible light from the biaxially stretched norbornene-based film side using an active energy ray irradiation device, and the biaxially stretched norbornene-based film was peeled off to obtain a laminated optical film.
[0132] The materials constituting the adhesive composition are as follows: Polymerizable compound A: (product name "UV3000B", manufactured by Mitsubishi Chemical Corporation) (logPow; 12.7) Polymerizable compound B: (triisopropyl glycol diacrylate) Trade name "Aronix M-220", manufactured by Toagosei Co., Ltd., LogPow; 1.68) Polymerizable compound C: (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate (product name "MEDOL-10", manufactured by Osaka Organic Chemical Industry Co., Ltd.) (logPow; 1.51) Polymerizable compound D: Lauryl acrylate (product name "Light Acrylate LA", manufactured by Kyoeisha Chemical Co., Ltd., LogPow;6) Polymerizable compound E: (phenoxydiethylene glycol acrylate) (product name "Light Acrylate P2H-A", manufactured by Kyoeisha Chemical Co., Ltd.) (logPow; 2.15) (refractive index; 1.517) Polymerizable compound F: (3-phenoxybenzyl acrylate) (product name "Light Acrylate POB-A", Kyoeisha Chemical Co., Ltd.) (logPow; 3.91) (refractive index; 1.566) Initiator 1 (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide): (Product name: Omnirad819 Manufacturer: IGM Resins BV)
[0133] (Appearance evaluation (evaluation of the presence or absence of oxalic acid bright spots)) A sample for evaluating humidity durability test was prepared by bonding the manufactured laminated optical film to one side of a 0.7 mm thick non-alkali glass sheet via an adhesive layer (thickness 20 μm). The sample was placed in an environment of 85°C-85% humidity and then exposed for 500 hours to carry out a humidity durability test. Using a differential interference microscope, a 2 mm x 3 mm area with the most oxalic acid bright spots was trimmed from within a range of 5 mm from the end face of the sample at a magnification of 5 times, an exposure time of 760 μs, and a gain of 1 time, and counted using ImageJ ver. 1.8.0. The number of bright spots was marked as "◯" when there were less than 15 bright spots, "△" when there were 15 to 30 bright spots, and "×" when there were more than 30 bright spots. The results are shown in Table 1.
[0134] (Initial peel strength (initial adhesive strength)) The obtained laminated optical film was cut into a size of 200 mm x 15 mm, and the laminated optical film was attached to a glass plate. Then, a cutter knife was used to make a cut between the acrylic film and the first optical film, and the acrylic film and the first optical film were peeled off in a 90-degree direction at a peeling speed of 10,000 mm / min using a Tensilon, and the peel strength (N / 15 mm) was measured. When the acrylic film or the first optical film broke or the peel strength exceeded 1.5 N, it was marked as "◎", when the peel strength was 1 to 1.5 N, when it was "△", when it was 0.5 N or more and less than 1 N, and when it was less than 0.5 N, it was marked as "×". The results are shown in Table 1.
[0135] (Peel strength under humid conditions (adhesive strength under humid conditions)) The obtained laminated optical film was left in an oven at a temperature of 20°C and a humidity of 98% for 240 hours, and then the laminated optical film was cut into a size of 200 mm x 15 mm, and the laminated optical film was attached to a glass plate. Then, a cutter knife was used to make a cut between the acrylic film and the first optical film, and the acrylic film and the first optical film were peeled off in a 90-degree direction at a peeling speed of 10,000 mm / min using a Tensilon, and the peel strength (N / 15 mm) was measured. When the acrylic film or the first optical film broke or the peel strength exceeded 1.5 N, it was marked as "◎", when the peel strength was 1 to 1.5 N, when it was "◯", when it was 0.5 N or more and less than 1 N, it was marked as "△", and when it was less than 0.5 N, it was marked as "×". The results are shown in Table 1.
[0136] [Table 1]
[0137] In Table 1, "average logPow" refers to "logPow, which represents the octanol / water partition coefficient, calculated as a weighted average of the molar fractions of the monomer components contained in the adhesive composition."
[0138] The results in Table 1 show that the laminated optical films of Examples 1 to 4 suppress the occurrence of bright spots due to foreign matter even after the humid durability test, have excellent appearance characteristics, and have excellent adhesive strength between the laminated optical films.
Claims
1. A laminated optical film in which at least an acrylic film and a first optical film are laminated via an adhesive layer, the adhesive layer is formed of a cured layer of an adhesive composition containing at least a polymerizable compound, The acrylic film and the adhesive layer have a structure in which they are in direct contact with each other, the adhesive composition has a logPow, which represents an octanol / water partition coefficient calculated by a weighted average of the mole fractions of the polymerizable compounds contained therein, of 1.8 or more and 3.0 or less; The elastic modulus of the adhesive layer is 1×10 5 Pa or more and 3×10 6 The laminated optical film has a modulus of elasticity of 1.0 Pa or less.
2. The laminated optical film according to claim 1 , wherein the first optical film is a liquid crystal film or a retardation film.
3. 2. The laminated optical film according to claim 1, wherein the adhesive layer has a thickness of 0.1 to 10 μm.
4. 2 . The laminated optical film according to claim 1 , further comprising a second optical film laminated via a pressure-sensitive adhesive layer on a surface of the first optical film opposite to the surface on which the acrylic film is laminated.
5. The laminated optical film according to claim 4 , wherein the second optical film is a liquid crystal film or a retardation film.
6. The adhesive composition contains a polymerizable compound A, The polymerizable compound A is a urethane (meth)acrylate having a molecular weight of 5000 or more and having at least two polymerizable groups, The laminated optical film according to claim 1 , wherein the content of the polymerizable compound A is 4 parts by mass or more and 30 parts by mass or less when the total amount of the polymerizable compounds contained in the adhesive composition is 100 parts by mass.
7. The adhesive composition contains a polymerizable compound B, The polymerizable compound B is a compound having at least two polymerizable groups, The laminated optical film according to claim 1 , wherein the content of the polymerizable compound B is 0 parts by mass or more and 15 parts by mass or less when the total amount of the polymerizable compounds contained in the adhesive composition is 100 parts by mass.
8. The adhesive composition contains a polymerizable compound C, The polymerizable compound C has a log Pow, which represents an octanol / water partition coefficient, of 1.0 or more and 8.0 or less, The laminated optical film according to claim 1 , wherein the content of the polymerizable compound C is 50 parts by mass or more and 95 parts by mass or less when the total amount of the polymerizable compounds contained in the adhesive composition is 100 parts by mass.
9. The adhesive composition contains a polymerizable compound D, The polymerizable compound D is a compound having a refractive index of 1.5 or more and 1.7 or less, The laminated optical film according to claim 1 , wherein the content of the polymerizable compound D is 0 parts by mass or more and 95 parts by mass or less when the total amount of the polymerizable compounds contained in the adhesive composition is 100 parts by mass.
10. An image display device comprising at least one laminated optical film according to claim 1.
Citation Information
Patent Citations
Curable adhesive for polarization film, polarization film, optical film and image display device
JP2015064575A
Liquid crystal panel and polarizer laminate used for liquid crystal panel
JP2015111236A
Active ray type inkjet ink and method for forming inkjet image
JP2017132939A
Polarizing film, optical film, and image display device
JP2022017074A
Active energy ray polymerizable adhesive and laminate
JP6862995B2